Silence in the Archives: France, the Algerian War, and National Identity - Hirschler, Maia (Archivaria)

(untitled) (Association of Canadian Archivists, 2025)
In 2021, French President Emmanuel Macron announced that the French government would make classified archives about the Algerian War accessible 15 years ahead of schedule, in an effort to improve Franco-Algerian relations. The announcement, which came after decades of requests that the archives be returned to Algeria, seemed to be a good-faith effort to address France’s difficult heritage with respect to the Algerian War (1954–1962) – particularly the widespread use of torture and the “disappearing” of dissidents during the war. The Algerian War has always occupied a contentious place in French history, having been largely left out of history textbooks and referred to as a war only after 1999. By opening the archives ahead of schedule, Macron seemed to commit the French government to healing generational wounds and improving relations with Algeria. The declassification of Algerian archives led the status of the Algerian War and, as a result, that of Algerian immigrants in contemporary France, to become major talking points for candidates on the right and on the left during the 2022 presidential election. While the opening of the archives appears to have done away with the archival silence that has shrouded the history of the war, this article will argue that France and its political actors have selectively lifted archival silence to privilege certain narratives and continue to silence others.